Job Satisfaction as A Driver of Organizational Commitment - Rahwana, Kusuma Agdhi; Yuniar, Evilia Sri (Faculty of Economics and Business, Jenderal Soedirman University, 2023)
The purpose of this study was to determine and analyze the effect of work motivation and job satisfaction simultaneously or partially on the Organizational Commitment of the Karangjaladri Village Farmer Group. Where farmers are lazy to farm and cannot carry out the program that has been prepared by the farmer group management, because it is recorded that an area of 105 hectares of rice fields is often traversed by tides which cause many farmers to experience crop failure. So that the land is now abandoned/unused and the farmers suffer losses and cannot keep their commitment to managing their fields. The number of population and samples that will be used as research objects are members of the Karangjaladri Village Farmer Group, which are 42 people. Data collection techniques used in this study were questionnaires and interviews. Hypothesis testing in this study using multiple regression analysis, correlation, and determination. The results showed that there was a significant effect either simultaneously or partially between work motivation and job satisfaction on organizational commitment in the Karangjaladri Village Farmers Group. The greatest influence is found in the variable job satisfaction on organizational commitment.